Modern scientific concepts of Zika fever - Viktor L. Melnikov; Larisa N. Aftaeva; Anastasia V. Sergeeva; Daria S. Bezmenova; Olesya S. Lebedeva (Clinical Medicine (Russian Journal), 2026)
The review article presents epidemiological, etiopathogenetic, clinical, and diagnostic aspects of Zika fever, as well as possible measures for the prevention and treatment of this infectious disease. The Zika virus (ZIKA) is transmitted through various routes, including vector-borne, vertical, sexual, and hemato-transfusion, which determines the clinical presentation of patients, the high rate of fetal death, and the development of severe congenital malformations. Currently, there is no specific etiotropic therapy for the treatment of Zika fever, and only a limited number of drugs that affect flavivirus viruses are used in clinical practice. Therefore, ZIKV remains a priority object for research in virology and epidemiology.